Market reform of Yunnan electricity in southwestern China: Practice, challenges and implications. (October 2019) - Liu, Shuangquan; Yang, Qiang; Cai, Huaxiang; Yan, Minghui; Zhang, Maolin; Wu, Dianning; Xie, Mengfei
Abstract: This paper reviews the electricity market reforms improving resource allocation and renewable energy integration in Yunnan. Given the predominance of hydropower and the importance of energy exports in Yunnan, the province presents a challenging case study of electricity market reforms. The experience of and lessons from Yunnan provide a reference for other provinces in China engaged in the growing adoption of renewable energy. The main contributions of this paper lie in the extension of the existing understanding of electricity reforms in Yunnan and China. Based on extensive data previously unreported in the literature, this paper shows how the Yunnan electricity market functions in practice and indicates where the practice is deficient in terms of the theory of how electricity markets should function. Finally, this paper suggests how market reforms should be adopted toward a scientifically designed electricity market. Highlights: Over 30 billion RMB of benefits have been produced by Yunnan's electricity market reforms. Provincial trading increased fourfold in five years based on a mid/long-term market supplemented by day-ahead trading. Interprovincial trading has been promoted via market mechanisms with a model of " plan  +  market ". Challenges and policy implications of further reforms are discussed.